Blue Shift in the Oriented Cuprous Oxide Micro Structures Prepared via PEG-400 as the Soft Template by γ-Irradiation - Liu, Weijun; He, Zhicai; He, Guanghong (Asian Journal of Chemistry, 2011)
Cuprous oxide (Cu2O) crystals with platelates structures were synthesized via γ-irradiation reducing reaction under ambient conditions, the polyethylene glycol-400 (PEG-400) as nonionized surfactant and ethylenediamine tetraacetic acid disodium salt (Na2EDTA) as chelator of Cu2+ ions. XRD and FESEM were used to illustrate Cu2O crystals with platelates structures. The products were also been characterized by HRTEM, ED analysis and UV-VIS absorption spectrum. All the results indicated that the Cu2O crystals with platelates were successfully prepared under γ-irradiation. The possible mechanism is that the existence of EDTA ions and polyethylene glycol may make growth rate along the <111> direction far exceeding that of the <100> direction, leading to the formation of platelate structure Cu2O at last. Its UV-VIS absorption peak revealed blue shift phenomena, with the corresponding band gap of 2.25 eV, the size effect resulted in an obvious blue shift.